MODELLING MANAGEMENT OF MOTIVATION OF PROFESSIONAL ACTIVITIES FOR TEACHERS IN A PRE-SCHOOL EDUCATION INSTITUTION - Tomashevs’ka Іryna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The modernization of preschool education is based on the standard of the new generation, the realization and implementation of which is impossible without improving the management of the quality of preschool education organizations. The article analyses contemporary forms and methods of monetary and non-monetary labour motivation of the employees of the sphere of that pre-school education as an important factor in improving the efficiency of labour. Nowadays improving the quality of education in preschool education institutions is a socially significant problem which pedagogical sciences and practice face. The purpose of the paper is to analyse the problem of motivation of professional development of preschool teachers as a condition for improving the quality of preschool education in the context. This research is set to: determine the factors affecting the motivation of teachers of preschool education institutions, to identify the stages of improvement of the system of motivation of preschool education specialists. Methodology of the study is based on the use of a set of methods determined by the peculiarity of the research problem: analysis of domestic and foreign scientific literature, synthesis, systematization, generalization, abstraction, as well as the interpretative and analytical method, which are used to provide theoretical analysis of the source base. The article shows that the pre-school education system is a particular institution for the formation of the personality of the younger generation. The role of teachers who work with children cannot be underestimated. The quality and effectiveness of teachers are largely determined by their motivation to perform educational work. The authors show that within the framework of pedagogic management it is important to find effective approaches to motivate staff of preschool educational organizations. It has its own peculiarities connected, on the one hand, with the government regulation in this sphere of activity, and, on the other hand, with the specific goals of the organization, the socioeconomic realities of its functioning and development, personal and professional characteristics of the staff. The authors of the article prove that management of motivation is a constant process which requires continuous improvement of the motivation system of staff and its parts taking into account the results of the diagnosis of the existing system, standards, existing external and internal constraints, characteristics of tangible and intangible benefits, permanent monitoring the work of each part of the system, with an assessment of their effectiveness. The authors provide factors that affect the motivation of staff of preschool educational organizations. These factors are divided into objective, with a limited influence from the management of the organization, and subjective, being in their sphere of influence. The subjective factors are presented through an external reflection, when teachers need public recognition of their merits, complexity and multidimensional nature of their work, and through the internal reflection when a teacher needs to maintain and develop the desire and opportunities for professional growth. The author offers the diagnostic techniques for studying motivation and professional activity effectiveness in the preschool educational institution, as well as the system of measures that allow educational organizations to change their work, increase teachers’ motivation and, as a result, to raise the effectiveness of their activities. We have grounded the author’s approach to the integral mechanism of motivation of pedagogical workers’ professional activity, orientated towards activation of pedagogical workers on the basis of study of their necessities, interests, personal aims and possibilities of their integration with the aims of the educational establishment as well as the usage of structural elements of different motivation models in management.